ANALISIS PERPANJANGAN RUNWAY BANDAR UDARA INTERNASIONAL ADI SOEMARMO SOLO JAWA TENGAH - Hudhiyantoro, Hudhiyantoro; Moetriono, Hary; Suryani, Any (Universitas 17 Agustus 1945 Surabaya, 2021)
AbstractSolo City is one of the cities that has the largest airport in Central Java, namely Adi Soemarmo International Airport. Adi Soemarmo Airport has a runway length of 2600 m x 45 m. To make the city of Solo a hub in Java, where major cities outside Java, especially East and West Indonesia can land directly in Solo, Adi Soemarmo Airport requires development. Adi Soemarmo Solo Airport development is planned to add flight routes and international passengers (Source: http://www.dephub.go.id).Based on the results of calculations that refer to the International Civil Aviation Organization (ICAO) standard with Boeing 777-300ER and 747-100 planes, a runway length of 3,700 m is needed. For runway capacity, the annual demand of 31,676 operations per year is smaller than the annual service volume of 210,000 operations per year so that the runway capacity has not been exceeded.To determine runway pavement thickness using planes with the largest single wheel load, namely B747-100 so that B-777-300ER is not used. For pavement thickness using Equivalent Aircraft Method from FAA with CBR Method Flexible Pavement B-747-100 graph calculation. Results:The total pavement thickness is 31 in ? 89 cm, Surface thickness (P-403 HMA) of 5 in ? 13 cm, Base course thickness (P-304 Cement Treat Base) is 6 in ? 15 cm, The thickness of the subbase course (P-154 sub-course) is 24 in ? 61 cm. For the calculation of drainage, the result is a closed channel (pipe) with an inlet dimension of 0.25 m x 0.25 m with a distance between 50 m inlet. AbstrakKota Solo merupakan salah satu kota yang memiliki bandara terbesar di Jawa Tengah yaitu Bandara Internasional Adi Soemarmo. Bandara Adi Soemarmo memiliki panjang landasan pacu 2600 m x 45 m. Untuk menjadikan Kota Solo sebagai hub di Jawa yang kota-kota besar di luar Jawa khususnya Indonesia Timur dan Barat dapat mendarat langsung di Solo, Bandara Adi Soemarmo membutuhkan pembangunan. Pembangunan Bandara Adi Soemarmo Solo direncanakan untuk menambah rute penerbangan dan penumpang internasional (Sumber: http://www.dephub.go.id).Berdasarkan hasil perhitungan yang mengacu pada standar International Civil Aviation Organization (ICAO) dengan pesawat Boeing 777-300ER dan 747-100, dibutuhkan panjang landasan sepanjang 3.700 m. Untuk kapasitas runway, kebutuhan tahunan sebesar 31.676 operasi per tahun lebih kecil dari volume layanan tahunan sebesar 210.000 operasi per tahun sehingga kapasitas runway belum terlampaui.Untuk menentukan ketebalan perkerasan runway menggunakan pesawat dengan beban roda tunggal terbesar yaitu B747 -100 sehingga B-777-300ER tidak digunakan. Untuk ketebalan perkerasan menggunakan Metode Pesawat Udara Ekuivalen dari FAA dengan metode CBR Metode Perkerasan Fleksibel B-747-100 perhitungan grafik. Hasil:Ketebalan total perkerasan jalan adalah 31 inci ? 89 cm, Ketebalan permukaan (P-403 HMA) 5 in ? 13 cm,Ketebalan lapisan dasar (P-304 Cement Treat Base) adalah 6 inci ? 15 cm, Ketebalan dari subbase course (P-154 sub-course) adalah 24 inci ? 61 cm. Untuk perhitungan drainase didapatkan saluran tertutup (pipa) dengan dimensi inlet 0,25 m x 0,25 m dengan jarak inlet antara 50 m.